Dynamics and Population Structure of Bali Cattle Partnerships Maiwa Breeding Center (MBC) in Barru Regency - Hasman; Sudirman Baco; Zulkharnaim (Hasanuddin Journal of Animal Science (HAJAS), 2021)
This study aims to determine the population dynamics, population structure, and increase of Bali cattle population Maiwa Breeding Center partnerships in Barru Regency. This research was conducted from March to April 2020 in Barru Regency, South Sulawesi. The Reproductive Efficiency of Bali cattle was 91%. Population dynamics were only influenced by the calving, mortality, and sale of livestock, with the growth of 27% (2019) and 31% (2020). The population structure was dominated by cows, 31% (2018), 48% (2019), and 54% (2020). Natural Increase (NI) of livestock was 17% (2018), 28% (2019) and 20% (2020). The conclusion of this study is that the growth of the Bali cattle population of MBC partnerships was still low when according to calving and income because it does not reach 80% of cows based on population even shows a tendency to decrease calving. Keywords: Population of dynamics, population of structure, Bali cattle, smallholder partnerships